9P-150型膨化机膨化螺杆载荷及磨损仿真研究 - 谢苗; 贾凯; 王书举; 刘治翔; 毛君 (Jixie qiangdu)
In view of the short life of the straw extruder with 9P-150 single screw due to serious wear,the mechanical analysis and wear mechanism of the straw extruder under the condition of determining abrasive properties were studied.EDEM software was used to simulate the stress and wear of the screw.The conclusions obtained in this paper will lay a theoretical foundation for the optimization of screw stress and wear condition.